Edukasi Dampak Pernikahan Dini Terhadap Kesehatan Reproduksi Remaja Wanita - Parwata, Ni Made Ridla Nilasanti; Izzah, Nurul (Politeknik Kesehatan Kementrian Kesehatan Palu, 2022)
Early marriage often occurs in Indonesia, especially in rural areas. If this condition continues, it will have a negative impact, especially on the health of the female reproductive system. Health education regarding the impact of early marriage on the female reproductive system must continue to be encouraged to prevent the increase in the number of marriages, especially in rural areas. insight and knowledge of adolescents regarding the impact of early marriage on the reproductive system of adolescents women who were attended by 21 participants. This activity was carried out in Tete Village, Ampana sub-district with the education method for 21 adolescents participants. The results of the activity showed that after education the level of knowledge of young regarding the impact of early marriage on the reproductive system of adolescents women increased from 9.5% to 71%, and most of the participants were able to answer the questions given at the end of the counseling activities properly and correctly. So it is expected that increasing the knowledge of adolescents regarding the impact of early marriage on the reproductive system of adolescents women can minimize the rate of early marriage. Suggests that education about reproductive health is often carried out to help adolescents make the right decisions in maintaining reproductive health.